Case Report: A novel IKBKB variant (c.1705G>T) is associated with immune dysregulation and disseminated tuberculosis - Arce-Estrada, Gabriel Emmanuel; Rodríguez-Morales, Miguel; Scheffler-Mendoza, Selma Cecilia; Sáez-de-Ocariz, Marimar; Berrón-Ruiz, Laura; Espinosa-Padilla, Sara Elva; Contreras-Verduzco, Francisco Alberto (Frontiers in Immunology, 2025)
ObjectiveTo describe a novel IKBKB variant linked to immune dysregulation and disseminated tuberculosis, alongside a review of pathogenic variants to outline their phenotypic spectrum.Material and methodsObservational case report and literature review.ResultsA five-month-old girl from an endogamous Mexican population developed symptoms suggestive of Kawasaki disease which progressed to hemophagocytic syndrome. Mycobacterium bovis was found in her skin, blood, and bone marrow. She had received the Bacillus Calmette-Guérin (BCG) vaccine on the second day of life. Genetic testing revealed a homozygous pathogenic variant (PV) in the IKBKB gene (c.1705G>T, p.Glu569*). Both parents were heterozygous. Fourteen publications were found, encompassing 33 patients with 14 different PV, including the case described in this work.DiscussionHypogammaglobulinemia, candidiasis and mycobacterial infections were common in most cases identified. Our case is unique in presenting with Kawasaki disease, hemophagocytic syndrome, and mycobacteria from skin, blood, and bone marrow.ConclusionsWe identified a novel homozygous PV in the IKBKB gene, highlighting new clinical manifestations.